STUDENTS’ CRITICAL THINKING IN DETERMINING COEFFICIENTS OF ALGEBRAIC FORMS - Aci Maria Jehaut Putri; Yus Mochamad Cholily; Putri Ayu Kusgiarohmah (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2020)
This paper reports the study of the critical thinking skills of 7th-grade students in junior high school on determining the coefficients of algebraic operation. Data were collected using worksheet and interviews. 34 students were involved during the study. The study reveals that there were 35% students who performed algebraic operations correctly. Students’ difficulty is mainly on determining the coefficients associated with the algebraic forms. In general, errors occur in the process of finding algebraic solutions, explaining the reasons for the stages of strategies taken and drawing conclusions. This is due to the fact that the main attention was given to the final result of the process of working on algebraic form problems, and less focus was paid on giving reasons for the process of working on problems that stimulate the students to think critically.